Compassionate Nursing Care Model: Results from a grounded theory study - Ghafourifard, Mansour (Nursing ethics, 2022)
Compassion, as an indicator for quality care, is highly valued by patients and healthcare professionals. Compassionate care is considered a moral dimension of nursing practice and an essential component of high quality care. This study aimed to answer these questions: (1) What are the facilitators and barriers of providing compassionate nursing care in the clinical setting? (2) Which strategies do nurses use to provide compassionate care? (3) What is the specific model of compassionate care for the nursing context? A grounded theory approach was used in this study. A total of 21 nurses working in diverse clinical settings participated in the study. Purposive and theoretical sampling was used to select the participants. Data were collected by in-depth face to face interviews and analyzed by the constant comparative method. Ethical approval was gained from the Ethical Review Board of Tabriz University of Medical sciences. The analysis resulted in the development of three main themes: (a) contextual factors affecting compassionate care, (b) the compassionate care actions, and (c) the consequences of compassionate care. The main dimensions of compassionate care are demonstrated in a Compassionate Nursing Care Model. Nurses’ ability on providing compassionate care is influenced by individual and organizational factors that may facilitate or inhibit this type of care. Leadership and nurse managers should remove the barriers which diminish the nurses’ ability to provide compassionate care and support them to engage in compassionate care programs. Identifying and recruiting compassionate nurses, developing their compassionate capacity, and providing role models of compassion could improve the flourishing of person-centered and compassionate care in clinical settings. The Compassionate Nursing Care Model (CNCM) provides a model to guide nursing care and research.